How Do Shared Experiences of Economic Shocks Impact Refugees and Host Communities? Evidence from Afghan Refugees in Iran - Hoseini, Mohammad; Dideh, Mahsa Jahan (World Bank, Washington, DC, 2022)
Using representative survey data including Iranians and Afghan refugees in Iran in 2011–2019, this paper explores the unequal impact of macroeconomic fluctuations due to Iran’s nuclear dispute on Afghan refugees and host communities. The paper finds that economic shock increases refugee’s exit and disproportionately reduces their consumption expenditure and aid received from the host community. In addition, bad and good economic cycles create asymmetric impacts. While negative shocks affect the economic outcomes of two communities homogenously, it hurts social cohesion between them. In contrast, economic recovery benefits refugees relatively more in terms of consumption and income, but the impact on social cohesion measures is insignificant. The findings also suggest that in turbulent economic times, both inter-community and intra-community inequalities go up.